Residual activity and sorption of tebuthiuron in different soils - Ferreira, João H. Dos S. [UNESP]; Melo, Christiane A. D.; de Moraes, Matheus F. [UNESP]; E Silva, Ilca P. de F.; Chioderoli, Carlos A. (FapUNIFESP (SciELO), 2024)
Applications of tebuthiuron can increase the risks of environmental contamination and hinder the cultivation of sensitive species in succession. The objective of this work was to assess the residual activity and sorption of the herbicide tebuthiuron in soils with different physical and chemical attributes. The experiments were conducted in a completely randomized design with four replicates. The experiment for determining residual activity was conducted in a 2 × 7 factorial arrangement consisted of two herbicide doses (0.6 and 1.2 kg a.i. [active ingredient] ha-1) and seven sowing times (0, 60, 120, 180, 240, 300, and 360 days after herbicide application) in sandy loam and sandy clay loam soils. The experiment for evaluating sorption was conducted in a sandy loam soil and two clay loam soils with applications of increasing tebuthiuron doses (0.025, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.50, 0.60, 0.70, and 0.80 kg a.i. ha-1). Regarding residual activity, the herbicide’s effect of the decreased over time, with no toxicity detected 360 days after application (DAA), regardless of the soils and doses used. Sandy loam soils had lower sorption, resulting in lower shoot dry weight and plant height and in higher phytotoxicity 21 days after emergence. Residual activity was detected 360 DAA in the studied soils. Tebuthiuron sorption was higher in soils with higher organic carbon and clay contents.
Atividade residual e adsorção do tebuthiuron em diferentes solos
Keywords: carryover; herbicide dynamics; pesticide retention in soils; sugarcane